LABOUR MARKET AND SOCIAL POLICY IN THE JIU VALLEY - MIHAELA CAMELIA SCHMIDT (Annals of the University of Petrosani: Economics)
The paper contains an analysis of the labour market and social policies in the Jiu Valley from the perspective of its inhabitants.